MENUJU SEBUAH TEORI UMUM PEMASARAN - Anton Agus Setyawan (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2012)
This article discusses the urgency of general marketing theory. Marketing becomes avery developed and converged discipline. This is a challenge for marketing scholars to present anew approach in constructing theory. Unfortunately, the dominance of traditional approach inmarketing brings stagnation in the theory construction. Although, general marketing theory isstill a hope for marketing scholars, they should broadened their vision to new approach in theoryconstruction.